"Mas a vida é real e de viés": o exercício da preceptoria e o processo de educação permanente no PET-Saúde/GraduaSUS de Santos, São Paulo - Correa, Elaine Rocha [UNIFESP] (2019)
The Education Program of Working for Health (PET-Health) / GraduaSUS 2016-2017 consisted of a front of efforts of the Municipal Health Department (SMS) of Santos and the Federal University of São Paulo, Baixada Santista campus (UNIFESP / BS), in the discussion of health education and teaching-service integration, focusing on maternal-infant mortality (MMI). Unprecedented, this edition collaborated with the municipalities of Itanhaém, Santos and São Vicente, as well as students / teachers of the Physical Education, Nutrition, Psychology, Social Work and Occupational Therapy courses of UNIFESP and Medicine from the Centro Universitário Lusíada, consisted of three cycles of eight months each, which surrounded the three municipalities. This dissertation aimed to systematize and discuss the experience of exercise of preceptorship and the process of Permanent Education in Health (EPS) at PET- Health / GraduaSUS in Santos / SP. This is a qualitative and retrospective study whose data production came from three records: PET Activity Record, maintained by the researcher / coordinator of PET-Santos, with linear records of project development; field diary, about the research process and experiences in the master's degree; Report on Preceptors Awareness Workshops, a synthesis document of the awareness workshops with eight preceptors, from different training areas, who participated in the final cycle of PET-Santos. The analyzes were based on the notion of EPS in motion. The data from this investigation agree with the literature on the practice of health preceptorship regarding the positive points such as the contact with students, the approach of teachers in the field and the remuneration of workers and the negative points, such as the absence of teachers in the practice setting, students with little interest, lack of service infrastructure, poor recognition of the role of preceptor as part of the job, and late payment of scholarships. The EPS strategies were configured as a process of building encounters moments with professionals, to a certain extent against hegemonic to the specific focus of training prioritized by SMS. In the first cycle, there was a certain invisibility of the actions produced in the services, which gave rise to the doubts and insecurities of the preceptors in conducting the activities with the students, in the absence of teacher’s support. In the second cycle, the insertion of a monthly meeting of preceptors allowed the construction of listening moments and discussion of intervention possibilities. Although the idea of instrumentalization for the exercise of preceptorship still prevailed, it culminated in the proposition of working groups with all PET actors to discuss and systematize themes relevant to the MMI. In the last cycle, the workshops indicated a breakthrough in proposing a more dynamic and reflective periodic space for dialogue on preceptorship, especially regarding the understanding of services and routines, with the guarantee of meaningful activities for students. This experience points to EPS present in many PET action spaces, based on the path and encounter of many actors and events that occurred in the breaches and often unrecognized or without visibility in the challenging daily work of health. Formal and periodic spaces of dialogue have allowed them to raise questions about preceptorship and professional practices.